Development of Cyberlink Power Director Based Learning Media in the Material of Human Digestive System - Mulyani Rahayu (Indonesian Journal of Biology Education, 2020)
The need for developing Cyberlink Power Director learning media based on poetries and songs for students and teacher includes the need of videos that can be seen, heard well, and can be used repeatedly according to particular time and place. Moreover, the presentation of information can be understood clearly, can contain the contents of the material systematically and comprehensively, can improve students’ learning outcomes, and can investigate the effectiveness of this media for science subject in the material about digestive in human for the fifth graders of MI Muhammadiyah Donorejo, Secang District, Magelang Regency. This research is an R&D (Research and Development) using the ADDIE step. The Technique of data analysis uses the quantitative descriptive technique. The type of instrument used was a questionnaire filled out before and after implementation. The result of this study shows that the Cyberlink Power Director based on poetries and song is proven to be valid by expert, and also effective in improving students’ learning outcomes in science subject in the material about digestive components in human (paired-sample t test, p = 0.00 <0.05).